KEPEMIMPINAN KEPALA MADRASAH DALAM UPAYA MENINGKATKAN KINERJA GURU DIMTS AL BAYYINAH KABUPATEN DELI SERDANG - Lestari, Eva (UNISAN JURNAL, 2025)
The teacher is the most decisive component in the education system as a whole, which must receive central attention. This figure will always be a strategic spotlight when talking about education issues, because teachers are always associated with any component in the education system, especially in relation to the teaching and learning process. With a professional teacher, a further goal, namely improving student learning outcomes will be achieved. It is the principal’s duty as a leader to assist teachers in improving teacher professionalism and performance. While there are still many teachers who in carrying out learning activities have not met expectations. Therefore, the author needs to examine the pattern of Principal Leadership in an effort to improve teacher performance at MTs Al Bayyinah. This study uses a qualitative approach, while the data collection uses participant observation techniques, interviews, and documentation. For data analysis using three flow of activities, namely data reduction, data presentation and drawing conclusions. From the results of the study it was stated that the principal’s leadership was considered good, but had not had a positive impact on improving teacher performance at MTs Al Bayyinah While the performance of teachers at MTs Al Bayyinah is considered good, but has not run optimally as expected, this is due to the lack of teacher ability in preparing learning tools, especially Learning Implementation Plans, inadequate school facilities and infrastructure, and also the difficulties of teachers in creating educational interactions between students and teachers, as well as the difficulty of creating a conducive classroom. However, at the level of evaluation/assessment of learning outcomes, the average teacher has implemented it well and added remedial and enrichment programs